2016
DOI: 10.1016/j.genhosppsych.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Do primary care medical homes facilitate care transitions after psychiatric discharge for patients with multiple chronic conditions?

Abstract: Objective Primary-care-based medical homes may facilitate care transitions for persons with multiple chronic conditions (MCC) including serious mental illness. The purpose of this manuscript is to assess outpatient follow-up rates with primary care and mental health providers following psychiatric discharge by medical home enrollment and medical complexity. Methods Using a quasi-experimental design, we examined data from NC Medicaid-enrolled adults with MCC hospitalized with an inpatient diagnosis of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…The results of this study contrast with those of prior studies which indicated that the PCMH may be associated with better medication adherence [ 19 , 20 ], receipt of preventive screenings [ 20 ], and outpatient follow-up after psychiatric discharge [ 21 ] for non-elderly adults with mental illness. The differences in study findings, however, could be attributed to methodological differences between the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study contrast with those of prior studies which indicated that the PCMH may be associated with better medication adherence [ 19 , 20 ], receipt of preventive screenings [ 20 ], and outpatient follow-up after psychiatric discharge [ 21 ] for non-elderly adults with mental illness. The differences in study findings, however, could be attributed to methodological differences between the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior systematic reviews have found mixed results for the PCMH overall [ 14 – 18 ], but three retrospective cohort studies conducted with non-elderly adults with mental illness enrolled in the North Carolina Medicaid program indicated that the PCMH may have favorable effects on medication adherence [ 19 , 20 ], preventive screenings [ 20 ], and outpatient follow-up after psychiatric discharge [ 21 ]. A study conducted with 9,303 North Carolina Medicaid-enrolled non-elderly adults with depression and at least one other chronic condition found that enrollees who had a PCMH had better rates of antidepressant adherence than those without a PCMH [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study reemphasizes the importance of considering mental as well as physical needs of older adults in health service design and delivery. Health care systems continue to silo acute services into psychiatric and physical services, and in the community, primary care services focus primarily on physical health (Domino et al, 2016). Mental illness decreases the capacity of older adults to self-manage physical conditions, such as learning or remembering how to use respiratory medications, or monitor heart failure symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These results may also highlight additional tools that can be used to improve care coordination, including use of pharmacist case managers or the medical home model, which has shown success in improving care in persons with severe mental illness. [25][26][27][28] For example, having adults with multiple discordant chronic conditions (such as CMCs and schizophrenia) who receive prescriptions from multiple providers designate a pharmacist case manager or establishing a PCP-based medical home may be associated with reductions in the potential for drug interactions, duplicate drug therapies or laboratory tests and provider role confusion (although not explicitly modeled in this study) that may occur when multiple, uncoordinated prescribers are involved in care.…”
Section: Discussionmentioning
confidence: 99%